Circadian disruption of memory consolidation in Drosophila - Yin, Jerry C. P.; Cui, Ethan; Hardin, Paul E.; Zhou, Hong (Frontiers in Systems Neuroscience, 2023)
The role of the circadian system in memory formation is an important question in neurobiology. Despite this hypothesis being intuitively appealing, the existing data is confusing. Recent work in Drosophila has helped to clarify certain aspects of the problem, but the emerging sense is that the likely mechanisms are more complex than originally conceptualized. In this report, we identify a post-training window of time (during consolidation) when the circadian clock and its components are involved in memory formation. In the broader context, our data suggest that circadian biology might have multiple roles during memory formation. Testing for its roles at multiple timepoints, and in different cells, will be necessary to resolve some of the conflicting data.